Victim Precipitation Pekerja Seks Komersial dalam Tindak Pidana Perdagangan Orang: Analisis Kebijakan Hukum Pidana: terhadap Putusan Nomor 565/PidSus/2023/PN Jmb - Shafira, Pinkan Tania; Hafrida, Hafrida (Faculty of Law, Universitas Jambi, 2026)
The practice of prostitution in the context of human trafficking (TPPO) raises questions regarding the legal position of Commercial Sex Workers (CSWs) in the criminal justice system. This study aims to analyze legal policies regarding CSWs from the perspective of criminal law reform and examine the involvement of CSWs in Decision Number 565/Pid.Sus/2023/PN Jmb through the theory of victim precipitation. The novelty of this study lies in the simultaneous integration of the analysis of CSWs in prostitution practices, TIP, and victim precipitation theory, making the decision a reflection of the legal vacuum regarding the contribution of CSWs to TIP. This research is a normative juridical study with a statutory, conceptual, and case-based approach. The results show that provisions in the Criminal Code and laws and regulations are more restrictive for prostitution service providers, while regulations regarding CSWs tend to be limited to regional regulations. The analysis of the decision indicates the dominance of intention and situational factors over repulsion in determining involvement. This study concludes the need for criminal law reform that clarifies the legal position of CSWs and the application of a victimological approach by law enforcement officials to achieve fairer and more consistent law enforcement. Praktik prostitusi dalam konteks tindak pidana perdagangan orang (TPPO) menimbulkan persoalan mengenai posisi hukum Pekerja Seks Komersial (PSK) dalam sistem peradilan pidana. Penelitian ini bertujuan menganalisis kebijakan hukum terhadap PSK dalam perspektif pembaruan hukum pidana serta mengkaji keterlibatan PSK dalam Putusan Nomor 565/Pid.Sus/2023/PN Jmb melalui teori victim precipitation. Kebaruan penelitian ini terletak pada penggabungan analisis PSK dalam praktik prostitusi, TPPO, dan teori victim precipitation secara bersamaan dengan menjadikan putusan tersebut sebagai refleksi kekosongan hukum terkait kontribusi PSK dalam TPPO. Penelitian ini merupakan penelitian yuridis normatif dengan pendekatan perundang-undangan, konseptual, dan kasus. Hasil penelitian menunjukkan bahwa ketentuan dalam KUHP dan peraturan perundang-undangan lebih menjerat penyedia jasa prostitusi, sedangkan pengaturan terhadap PSK cenderung terbatas pada peraturan daerah. Analisis putusan menunjukkan dominasi faktor niat dan situasi dibandingkan daya tolak dalam menentukan keterlibatan. Penelitian ini menyimpulkan perlunya pembaruan hukum pidana yang memperjelas posisi hukum PSK serta penerapan pendekatan viktimologis oleh aparat penegak hukum guna mewujudkan penegakan hukum yang lebih adil dan konsisten.